THE RELATIONSHIP BETWEEN SCHOOL LEADERSHIP AND WORK DISCIPLINE WITH TEACHER JOB SATISFACTION AT SMA NEGERI CIRANJANG - Jakaria, Jakaria (Indonesian Journal of Adult and Community Education, 2022)
Principal leadership has a very important role in improving the work discipline of teachers who are good and obedient to the rules that apply in schools. To improve the quality of education a school principal must be able to increase the job satisfaction of teachers or their subordinates. Teacher work discipline is closely related to compliance in implementing school regulations. The purpose of this research is to: 1). Analyzing the relationship between the principal's leadership and teacher job satisfaction at SMAN 1 Ciranjang, Cianjur Regency, 2). Analyzing the relationship between teacher discipline and job satisfaction at SMAN 1 Ciranjang, Cianjur Regency 3) Analyzing the relationship between the principal's leadership and teacher discipline together with teacher job satisfaction at SMAN 1 Ciranjang, Cianjur Regency. The type of research being conducted was descriptive quantitative research. The research method used in this study uses an associative quantitative approach with survey methods. The sample in this study were all PNS teachers at SMAN 1 Ciranjang, Cianjur Regency in 2021. The sampling technique through a questionnaire was carried out based on the basic principles of the probability sampling technique through a random cluster sampling technique (area sampling). The analysis technique starts from the normality test, homogeneity test, simple linear regression test, and multiple regression test. Based on data analysis, it can be concluded: There is a positive relationship between the leadership of the Principal and Teacher Discipline together with teacher job satisfaction at SMAN 1 Ciranjang, Cianjur Regency.